Evolution of the Main Crater, Irazú Volcano National Park, Costa Rica – Consumer Drones in professional research - Godfrey, Ian (2022)
There has been significant cracking and erosion on the south crater wall of the Main Crater below the area where tourists gather to view the main feature of the park; The Main Crater. By deploying the EVO Lite+ drone system we will be able to document any increase in erosion or cracking within the Main Crater, we will search for areas subject to future rock falls within the Main Crater, the UAS observation strategy will also be innovative as it offers a new and unique perspective of the volcano summit and interior structures of the Main Crater. By using the Lite+ system we will check for lake water levels, areas of mineralization or crystallization, and any potential vents degassing volcanic emissions, we will look for subaquatic fumaroles releasing gases via bubbles and try to film them for frequency and size documentation. The qualitative analysis of the Irazú Volcano Main Crater will show changes in morphology and illustrate how consumer drones can be used for professional research.